Billie Jean King vs. Bobby Riggs - Skinner, J. E. (Sports unite us., 2019)
Profiles tennis star Billie Jean King and highlights her "Battle of the Sexes" against tennis champion Bobby Riggs, whom she beat and became famous for after. Includes a glossary.